Heritabilities and genetic correlations for birth weight, weaning weight, and yearling weight in polled Hereford cattle - Glaze, J.B.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Performance data from a Polled Hereford herd selected for feed conversion were used in the calculation of heritabilities and genetic correlations for birth weight (BWT), weaning weight (WWT), and yearling weight (YWT). Direct heritabilities for BWT, WWT, and YWT were .31, .16, and .25, respectively. Corresponding maternal heritabilities for BWT, WWT and YWT were .04, .01, and .18, respectively. With the exception of the correlation between WWT and YWT (.98), the other genetic correlations were low to moderate, ranging from -.27 to .12.
Keywords: Beef; Birth weight; Weaning weight; Yearling weight; Heritabilities; Genetic correlations